Feasibility Analysis of Smart Transportation as an Embodiment of Smart City in Madiun City - Aminah, Vindy Ananda; Afandi, Aang; Sari, Padma Adriana (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Implementing the Smart City program in the field of Smart Transportation continues to be improved and is an environmentally friendly solution. The implementation of this research aims to determine location governance, Madiun City Government, the amount of initial investment costs required, and the investment feasibility of this e-bike-sharing plan. The method implemented is descriptive quantitative based on DPP (Discounted Payback Period), IRR (Internal Rate of Return), and NPV (Net Present Value) to calculate investment feasibility analysis. The results showed that the location of the E-Bike Sharing shelter at the Station, Terminal, Alun-alun Madiun City. It is furthermore, related to the Government governance plan that the E-Bike Sharing plan is managed by the Madiun City Tourism, Youth and Sports Culture Office. The total initial investment cost of the E-Bike Sharing plan issued by the Madiun City Government amounted to Rp 1,416,426,706 which includes the cost of procuring E-Bike Sharing, building shelters, electricity supply costs, and supporting equipment costs. From the total investment value, it is known that the Net Present Value (NPV) value is Rp 1,806,108,550 or more than zero, the Internal Rate of Return (IRR) value represents that the result is 58.41% or not lower than the expected minimum rate of return of 6.4% and the Discounted Payback Period (DPP) value is 1 year 12 days or shorter than the project life of 4 years, so it can be concluded that the E-Bike Sharing project investment plan is feasible to run.